EFFECT OF USING SPECIAL EXERCISES TO DEVELOP OF A NUMBER OF COGNITIVE ABILITIES KINESTHETIC AND LEARNING FOOTBALL DRIBBLING SKILL - Younus, Ali Qutaiba (Holistic Journal of Sport Education, 2025)
Research aims to reveal impact of using special exercises in development of a number of cognitive abilities and learning skill of dribbling football. And to compare in post-test between two study groups in development of a number of cognitive abilities kinetic and learning skill of dribbling football for students of fifth grade of primary school, and researcher used experimental approach to suit nature of research, represented Community of research was students of Khank Elementary School (fifth grade), for (2023-2024) academic year, which numbered (146) students was distributed over four sections. The research sample was selected by lottery, as draw led to selection of divisions (B, D), and thus number of sample reached (62) students, as well as draw led to selection of students of Division (A) a sample for stability and pilot experiments and were excluded a number of student of sample for lack of equality with sample, and thus final number of sample (32) pupils divisive for two (experimental , control) groups at (16) pupils for each, a percentage was (21.917%) of a community of study. The suggested exercises were division by lottery. educational programs fulfillment it took eight weeks, divided at two units weekly, units time it was (40 m). In through research re returns ached by researcher that educational programs applied to two research groups have a positive impact on development of some cognitive abilities kinetic influential football. Experimental group, which used special skill exercises focused on motor sensation, outperformed control group, which used traditional method (skill exercises program only). Advantage of development of cognitive abilities in experimental group was effectively reflected in improvement of learning process of skill of dribbling football. Researcher recommended emphasizing synchronization of cognitive development when embarking on learning basic football skills. And emphasis on development of cognitive abilities among young age groups in football. As well as emphasizing development of cognitive abilities when learning basic skills in other group events, and conducting studies and research to develop cognitive abilities for different age stages.